Pelaksanaan Mediasi Bagi Para Pihak Dalam Perkara Perceraian - Rahmiati Rahmiati; Kairuddin Karim; Auliah Ambarwati (Jurnal Litigasi Amsir, 2024)
This research delves into the implementation of divorce case mediation at the Enrekang Religious Court, emphasizing the pre-mediation stages, mediation implementation, and final reporting to the case judge. Findings reveal a structured process involving problem identification, proposal of alternative solutions, and consultation. The mediator is mandated to report mediation outcomes and legal consequences, including a written agreement signed by parties. In cases of agreement, parties present the signed agreement to the judge, potentially leading to a peace decision. The Settlement Agreement, validated by a Deed of Settlement, adheres to court disclosure regulations.